Mechanical properties and fabrication of small boat using woven glass/sugar palm fibres reinforced unsaturated polyester hybrid composite - Misri, Sairizal; Leman, Zulkiflle; Salit, Mohd Sapuan; Ishak, Mohamad Ridzwan (IOP Publishing, 2009)
In recent years, sugar palm fibre has been found to have great potential to be used as fibre reinforcement in polymer matrix composites. This research investigates the mechanical properties of woven glass/sugar palm fibres reinforced unsaturated polyester hybrid composite. The composite specimens made of different layer of fibres such as strand mat, natural and hand woven of sugar palm fibres. The composites were fabricated using a compression moulding technique. The tensile and impact test was carried out in accordance to ASTM 5083 and ASTM D256 standard. The fibre glass boat is a familiar material used in boat industry. A lot of research on fabrication process such as lay-up, vacuum infusion mould and resin transfer mould has been conducted. Hybrid material of sugar palm fibre and fibre glass was used in fabricating the boat. This research investigates the method selection for fabrication of small boat application of natural fibre composites. The composite specimens made of different layer of fibres; woven glass fibre, strand mat, natural and hand woven of woven sugar palm fibres were prepared. The small boat were fabricated using a compression moulding and lay up technique. The results of the experiment showed that the tensile strength, tensile modulus, elongation at break value and impact strength were higher than the natural woven sugar palm fibre. The best method for fabricating the small boat was compression moulding technique. As a general conclusion, the usage of glass fibre had improved the tensile properties sugar palm fibre composites and compression moulding technique is suitable to be used in making a small boat application of natural fibre composites.